Pengaruh Food Vlogger Sebagai Social Media Influencer Terhadap Minat Beli Produk Makanan Di Kalangan Followers Gen Z Di Lamongan (Studi Kasus Korean Food di Kabupaten Lamongan): (Studi Kasus Korean Food di Kabupaten Lamongan) - Zurotul Jannah, Mita; Shofia Maulida, Indira; Susanti, Ike; Ruswaji (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
In the city of Lamongan there is currently a proliferation of food vloggers/influencers on the social media Instagram who provide reviews about good food or drinks. from outside or from Lamongan itself. The purpose of this research is to determine the influence of Argument Quality, Credibility, Attractiveness on Intention to Buy food products among Gen Z followers in Lamongan Regency, simultaneously and partially, which coincides with Boboho Korean Street Food Lamongan. In this study the author used Gen Z Followers as the population. The sample in this study consisted of 100 respondents who were calculated using the Slovin method. This research is classified as using a quantitative method with a sample size of 100 respondents. By using a direct survey method through distributing questionnaires as a way to obtain data. The method used to analyze this research data was SPSS version 26. The respondents in this research were Gen Z Followers in Lamongan Regency. The test results in this study show that the T Test of the argument quality variable Tcount > Ttable with a value of 3,572 > 1.984, the Credibility variable Tcount > Ttable with a value of 5,362 > 1.984, the attractiveness variable Ttable > Tcount with a value of 5,573 > 1,984. and the Multiple Linear Regression Test Y = 1.119 + 0.213X1 + 0.205X2 + 0.424X3, it can be interpreted that the most dominant value is the Attractiveness variable of 0.424. The results of this research show that the Attractiveness variable is the most dominant variable in buying interest in food products among Gen Z followers in Lamongan Regency.